Poskeynesian view on production: Sraffa's criticism of neoclassic theory - Osorio Vaccaro, Jorge Guillermo (2021)
A fundamental aspect of the confrontation between Neoclassical orthodoxy and Post-Keynesianism is the Theory of Production. Post Keynesianism, in particular the Sraffians, have criticized the basis on which orthodoxy analyzes production (and, in fact, they criticize its fundamental vision of the economic system) that remains virtually unchanged in the new Neoclassical orthodoxy. Two important pillars of this critique that would give rise to what is known as the Controversy around the Theory of Capital are the Reversion of Capital and the Double Reversion Theorem, Sraffianos. Sraffa undermines the foundations of the Neoclassical theory of production in such a way that his criticisms of the coherence of the Neoclassical orthodoxy approach to the way factors of production are combined have not been strongly refuted to this day. Whether a given approach to the behavior of economics is inconsistent to explain fundamental parts of how markets operate, using it may not only be irrelevant, but even counterproductive if policies derived from such an approach are applied. Ms Sraffa's criticisms must be seriously revised to build realistic theories, and not reject them without in-depth analysis.